The princess diaries : give me five - Cabot, Meg (London : Macmillan Children's Books, 2003)
It's nearly Mia's fifteenth birthday. She should be getting ready for the Senior Prom, escorted by her boyfriend, Michael. But Michael hasn't even invited her to the prom yet. Hello, what exactly is going on there? Just as Mia cooks up a plan to change Michael's mind, disaster strikes. The kind of disaster that only a miracle can overcome.
Keywords: Princesses -- Fiction; Diary fiction